Can angiotensin converting enzyme inhibitors prevent postoperative adhesions? - Bulbuller, N; Ilhan, YS; Kirkil, C; Cetiner, M; Gogebakan, O; Ilhan, N (Academic Press Inc Elsevier Science, 2005)
Background. Peritoneal adhesions are pathological fibrotic bands developing after mesothelial damage. Transforming growth factor beta-1 (TGF-beta 1) has mitogenic activities for macrophages and fibroblasts. Overexpression of TGF-beta 1 has been implicated in the pathogenesis of several fibrotic disorders. Angiotensin II increases the expression of the TGF-beta 1 in fibroblasts. The aim of the study was to investigate the effect of angiotensin converting enzyme inhibitor (ACE) on intraperitoneal adhesions. Materials and methods. Thirty male Wistar albino rats were divided into two groups. In the first procedure, laparotomy was performed through a 3-cm midline incision. Ileum was divided above 10 cm from ileocecal valve and a single-layer ileoileal anastomosis was performed. Although no treatment was given to rats in group 1, lisinopril (an ACE inhibitor) was given to rats in group 2 for postoperative 7 days in drinking water. Estimated amount of supplied lisinopril was 6.5 mg/kg/day. On postoperative 8th day, relaparotomy was performed and adhesions were evaluated. At the same time, blood samples were taken for TGF-beta 1 measurements. Results. Adhesion severity was significantly less in the ACE inhibitor group (P < 0.001). While mean TGF-beta 1 level was 860.3 +/- 108.1 pg/dl (mean +/- SD) in control group, it was 335.8 +/- 52.4 pg/dl in ACE inhibitor group (P < 0.001). There was a significant correlation between serum TGF-beta 1 levels and grade of adhesions (r = 0.948). Conclusion. It was concluded that ACE inhibitors might be useful for preventing peritoneal adhesions. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: intraperioneal adhesion; angiotensin; converting enzyme inhibitor; lisinopril; transforming growth factor